ANALISIS FAKTOR YANG MEMPENGARUHI MANAJEMEN PAJAK DENGAN INDIKATOR TARIF PAJAK EFEKTIF (STUDI PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI TAHUN 2017-2020) - Destry Faradila Nur’avisa; Evi Yuniarti; Rusmianto Rusmianto (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2022)
This research to analyze of factors affect the tax management with indicators of effective tax rate on mining companies listed in Indonesia Stock Exchange. There are several factors used include size, profitability, fixed asset intensity, inventory intensity and investment opportunity set. This purpose of this study is to empirically examine whether the size, profitability, fixed asset intensity, inventory intensityand investment opportunity set affect the tax management. The sample of this research of 8 mining companies listed in Indonesian Stock Exchange of years 2017-2020. Determination of sample was made by applying purposive sampling. Analysis tool used multiple linear regression with F test, t test and the coefficient of determination was conducted using SPSS version 22. The result showed that the variable size, profitability, fixed asset intensity, inventory intensity, and investment opportunity set affect significantly simultaneously (F test) tax management. From the result of the analysis of partially (t test) the variable size, profitability, fixed asset intensity, inventory intensity did affect significantly to tax management, while the investment opportunity set influential did not significantly to tax management. The result of the coefficient determination showed 43,8% independent variable affect to dependent variable and 56,2% can be explain with the other variables.Keywords: Tax Management, Effective Tax Rate, Indonesia Stock Exchange